Left High and Dry: Deglaciation of Dogger Bank, North Sea, Recorded in Proglacial Lake Evolution - Emery, Andy R.; Hodgson, David M.; Barlow, Natasha L. M.; Carrivick, Jonathan L.; Cotterill, Carol J.; Phillips, Emrys (Frontiers in Earth Science, 2019)
Reconstructions of palaeo-ice sheet retreat in response to climate warming using offshore archives can provide vital analogues for future ice-sheet behaviour. At the Last Glacial Maximum, Dogger Bank, in the southern North Sea, was covered by the Eurasian Ice Sheet. However, the maximum extent and behaviour of the ice sheet in the North Sea basin is poorly constrained. We reveal ice-marginal dynamics and maximum ice extent at Dogger Bank through sedimentological and stratigraphic investigation of glacial and proglacial lake sediments. We use a large, integrated subsurface dataset of shallow seismic reflection and geotechnical data collected during windfarm site investigation. For the first time, an ice stream is identified at Dogger Bank, based on preserved subglacial bedforms, eskers and meltwater channels. During ice-sheet advance, a terminal thrust-block moraine complex formed, whose crest runs approximately north-northeast to south-southwest. Subsequent ice stream shutdown caused stagnation of ice, and rapid retreat of the ice-sheet margin. The moraine complex, and outwash head from an adjacent ice-sheet lobe to the west, dammed a large (approximately 750 km2) proglacial lake. Subsequent sedimentation infilled the lake with 30 m of glacial outwash sediments. A lobate subaqueous fan formed at the ice-sheet margin, which thins towards the southeast with iceberg scours and ice-rafted debris at the base, and is onlapped by lake sediments calibrated to core as alternating clay and silt laminae, interpreted to be varves. The lake became isolated from the retreating ice-sheet margin, and ice-sheet retreat slowed. Sediment-laden meltwater was supplied to the ice-distal proglacial lake for c. 1500-2000 years. Subsequent ice-sheet retreat off Dogger Bank was more rapid due to the negative subglacial slope. The stepped retreat of rapid downwasting, slow retreat, and a final rapid phase off Dogger Bank occurred after the LGM at around 27 ka and before formation of a ribbon lake, dated previously to 23 ka and approximately 60 metres lower in elevation, formed to the north of Dogger Bank. The complicated stratigraphic architecture revealed through these data improves forecasting of ground conditions for turbine footings at Dogger Bank, an important step in the provision of clean, sustainable energy.